Hidden gems [science and technology museums]. - Six, J.M (IEEE spectrum)
This paper announces the publication of the results of the survey conducted by IEEE Spectrum on several science and technology museums around the globe. Because of the Internet, IEEE members worldwide have been able to review 26 museums so far. The full text of their comments can be viewed at http://www.spectrum.ieee.org.